2020
DOI: 10.1016/j.tifs.2020.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Seaweeds as promising resource of bioactive compounds: Overview of novel extraction strategies and design of tailored meat products

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 148 publications
(114 citation statements)
references
References 99 publications
2
112
0
Order By: Relevance
“…Seaweeds have been added to meat products, such as burgers, frankfurters, pâtés, sausages, and steaks (Table 6). In these products, macroalgae have a double function: as antioxidants, preserving the quality of meat products; and as fat replacers, developing low-fat products [167]. In the first case, their powerful antioxidant properties are linked to the presence in their composition of bioactive compounds (alkaloids, carotenoids, polyphenols, terpenes, and tocopherols).…”
Section: Ros Antioxmentioning
confidence: 99%
“…Seaweeds have been added to meat products, such as burgers, frankfurters, pâtés, sausages, and steaks (Table 6). In these products, macroalgae have a double function: as antioxidants, preserving the quality of meat products; and as fat replacers, developing low-fat products [167]. In the first case, their powerful antioxidant properties are linked to the presence in their composition of bioactive compounds (alkaloids, carotenoids, polyphenols, terpenes, and tocopherols).…”
Section: Ros Antioxmentioning
confidence: 99%
“…Another potential alternative is edible seaweeds, which have been utilized as fat replacers in meat products. Studies have shown that incorporation of seaweeds and their derived compounds resulted in organoleptic properties similar to conventional products [36]. Thus, wide varieties of plant materials and methods exist for the development of meat substitutes.…”
Section: Technological Feasibilitymentioning
confidence: 99%
“…For extraction purposes based on ultrasound, high-frequency waves (>2 MHz) are applied which favor the formation of cavitation bubbles. This phenomenon is responsible for the disruption of the cellular structure of the sample, facilitating the contact between solvent and cellular material, which consequently improves the mass transfer and increases the extraction efficiency [ 68 , 69 ]. In recent years, some authors applied ultrasound to extract phenolics from Eucalyptus biomass.…”
Section: Extraction Procedures Of Polyphenols From Eucalmentioning
confidence: 99%